How do shuttle and slow-release effects of zinc fertilizers alter zinc diffusion in soil and its uptake by wheat plants? - Kaur, Sevendeep (Kansas State University, 2021)
Zinc deficiency is a widespread problem. To correct these deficiencies, different organic and inorganic Zn fertilizers have been used. Various sorption-desorption reactions control the Zn concentration in soil solution and Zn availability from these different sources to crops. The effectiveness of Zn fertilizers varies with soil type. Very soluble Zn fertilizer sources can undergo adsorption and precipitation losses upon soil application. Although these transformations are relatively minor, the chelated Zn source is not cost-efficient and could also be sensitive to leach in alkaline soils. In contrast, sparingly soluble Zn fertilizers can show poorer performance in neutral and low pH soils. Considering all these factors, a new granular Zn mix (mixture containing 60% ZnO, 25% ZnSO₄, and EDTA to ZnSO₄ 1:8 ratio) fertilizer was recently introduced. The objectives of this thesis work were to compare the efficiency of different Zn only sources in four different soils, two calcareous, one neutral and one acid, with varying pH with varying pH; and compare different Zn-coated urea fertilizers for two soils, one calcareous and one acid soil. Zinc diffusion from the point of application was measured using incubation, visualization, and greenhouse studies. Zinc plant uptake was measured in the greenhouse study using a high-Zn responsive wheat line. Along with the wet chemical analysis, advanced synchrotron-based X-ray absorption near-edge structure technique was also used to understand the Zn fertilizer reaction products better when added as different sources in soil. We found that Zn diffusion and Zn plant uptake were greater for ZnSO₄.7H₂O and ZnEDTA for neutral pH soil. Zinc mix performed similarly to the two most effective ZnO and ZnEDTA treatments in terms of plant biomass and plant Zn uptake in both calcareous soils, which are well known for Zn fixation. There were no significant differences in the Zn sources concerning plant uptake for acid soil. Regarding Zn-coated urea treatments, ZnO-U and ZnEDTA-U performed well in plant Zn uptake in acid soil. However, no significant differences were observed between any Zn-coated urea sources in calcareous soil and Zn-coated urea sources increased plant biomass and uptake irrespective of the source. Zinc-coated urea sources seemed to provide more plant available Zn due to the enhanced solubility facilitated by its urea co-additive. Results from our studies suggest that the suitable Zn source should be carefully selected for efficient mitigation of Zn deficiencies in different soils depending upon their physicochemical properties.
Keywords: Zinc; Soil chemistry; Micronutrients; Fertilizers; Synchrotron; XANES